1992
DOI: 10.1111/j.1365-3024.1992.tb00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines inhibit the development of trophozoite‐infected cells of Theileria annulata and Theileria parva but enhance the proliferation of macroschizont‐infected cell lines

Abstract: The following bovine (Bo) and human (Hu) cytokines--Bo rTNF-a, Bo rIFN-g, Hu IFN-a, Hu rIL-1, Hu rIL-2--significantly inhibited the in vitro development of trophozoite-infected cells of three stocks of Theileria annulata and of Theileria parva (Muguga). However, none of these cytokines inhibited the proliferation of established T. annulata or T. parva macroschizont-infected cell lines. Indeed, Bo rTNF-a and Hu rIL-2 consistently enhanced the proliferation of macroschizont-infected cell lines of both species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The high number of cytokine responders that succumbed to the challenge infection indicates that ex vivo IFN-␥ responses do not serve as a predictive marker of protection against severe disease or fatality. This observation is notable in the context of previous studies, which demonstrated an inhibitory effect of IFN-␥ on the development of the early schizont stage in vitro (20). Our data suggest that vaccineinduced CD8 ϩ lytic responses may contribute to survival from a lethal challenge infection and highlight possible distinct roles of IFN-␥-secreting and lytic CD8 ϩ T cells in immunity against ECF.…”
Section: Ctl Target Antigens Recognized By T Cells From Immune Cattlesupporting
confidence: 78%
“…The high number of cytokine responders that succumbed to the challenge infection indicates that ex vivo IFN-␥ responses do not serve as a predictive marker of protection against severe disease or fatality. This observation is notable in the context of previous studies, which demonstrated an inhibitory effect of IFN-␥ on the development of the early schizont stage in vitro (20). Our data suggest that vaccineinduced CD8 ϩ lytic responses may contribute to survival from a lethal challenge infection and highlight possible distinct roles of IFN-␥-secreting and lytic CD8 ϩ T cells in immunity against ECF.…”
Section: Ctl Target Antigens Recognized By T Cells From Immune Cattlesupporting
confidence: 78%
“…A possible role for CD4 + -positive T-cells in immunity to T. annulata may involve their production of macrophage-activating cytokines. Indeed, cytostatic macrophages have been demonstrated in T. annulataimmune cattle (Preston 1981;Preston and Brown 1985;Preston et al 1992b). On the basis of the capacity of such macrophages to produce TNF-a (Preston et al 1993) and NO (Visser et al 1995), it has been suggested that CD4 + cells produce IFN-c, which participates in the activation of such macrophages to produce NO and to kill the schizonts (Preston et al 1997;Richardson et al 1998).…”
Section: T-helper Cellsmentioning
confidence: 99%
“…More importantly, activated CD 4 T cells produce cytokines such as IL-2 and IFN-γ required for the clonal expansion of CTLs (Ahmed and Mehlhorn 1999;Forsyth et al 1997). In addition, IFN-γ stimulates bovine macrophages to synthesize TNF-α (Preston et al 1993), which is regarded as a modulator cytokine in host defense against protozoal Infections (Aggarwal et al 1985), leading to inhibition of trophozoite-infected cells as well as cytotoxic effects on macroschizontinfected cells (Preston et al 1992.…”
Section: Introductionmentioning
confidence: 99%